Evaluation of the field performance and genetic diversity of 23 varieties of okra from Bangladesh using RAPD markers - Hossain, Md Anowar; Hossen, Md Sajjad; Munshi, Arifur Rahman; Rahman, Kazi Zahidur; Karim, Md Rezaul; Kimura, Yoshinobu (Bangladesh Journal of Plant Taxonomy, 2020)
Abstract not available Bangladesh J. Plant Taxon. 27(1): 195-199, 2020 (June)